Optimisation of beef tenderisation by papaya juice using response surface methodology / Che Norhaslida Binti Che Ahmad - Che Ahmad, Che Norhaslida (Faculty of Applied Sciences, 2008)
The purpose of this study was to investigate the usage of papaya (officinale Carica Papaya L.) on the tenderisation of beef. Papaya juice was diluted in the range of 100 to 20%. Physiochemical properties of papaya juice such as pH, pulp content, juice yield, cloudiness and total soluble solid were determined by using pH meter, centrifuge, hand refractometer and uv-spectrometer respectively. It was found that the more diluted papaya juice, the higher values of pH and juice yield, but the percentage of pulp content, absorbance and total soluble solid were lower. By using Response Surface Methodology (RSM) of the MINITAB software version 14, experimental design could be created whereby test variables such as papaya juice concentration, temperature and time of immersion were used. Beef was immersed in different papaya juice concentrations and shaked in shaking water bath with temperature ranging 30oC to 70oC, for immersion times ranging from 5-25 minutes. The tenderisation of treated beef was immediately measured using Texture Analyser, TX-TA2i with P2N needle probe. The optimum conditions for beef tenderisation using papaya juice could be determined by response optimiser of response surface methodology. The highest increment tenderisation of beef treated with papaya juice was 77.5% in 91% papaya juice concentration, 39oC of immersion temperature and 6.8 minutes of immersion time.